Comparative evaluation of osteogenic differentiation potential of stem cells derived from dental pulp and exfoliated deciduous teeth cultured over granular hydroxyapatite based scaffold - Manal Nabil Hagar; Farinawati Yazid; Nur Atmaliya Luchman; Shahrul Hisham Zainal Ariffin; Rohaya Megat Abdul Wahab (BMC, 2021)
Abstract Background Mesenchymal stem cells isolated from the dental pulp of primary and permanent teeth can be differentiated into different cell types including osteoblasts. This study was conducted to compare the morphology and osteogenic potential of stem cells from exfoliated deciduous teeth (SHED) and dental pulp stem cells (DPSC) in granular hydroxyapatite scaffold (gHA). Preosteoblast cells (MC3T3-E1) were used as a control group. Methodology The expression of stemness markers for DPSC and SHED was evaluated using reverse transcriptase-polymerase chain reaction (RT-PCR). Alkaline phosphatase assay was used to compare the osteoblastic differentiation of these cells (2D culture). Then, cells were seeded on the scaffold and incubated for 21 days. Morphology assessment using field emission scanning electron microscopy (FESEM) was done while osteogenic differentiation was detected using ALP assay (3D culture). Results The morphology of cells was mononucleated, fibroblast-like shaped cells with extended cytoplasmic projection. In RT-PCR study, DPSC and SHED expressed GAPDH, CD73, CD105, and CD146 while negatively expressed CD11b, CD34 and CD45. FESEM results showed that by day 21, dental stem cells have a round like morphology which is the morphology of osteoblast as compared to day 7. The osteogenic potential using ALP assay was significantly increased (p < 0.01) in SHED as compared to DPSC and MC3T3-E1 in 2D and 3D cultures. Conclusion gHA scaffold is an optimal scaffold as it induced osteogenesis in vitro. Besides, SHED had the highest osteogenic potential making them a preferred candidate for tissue engineering in comparison with DPSC.